2001
DOI: 10.1046/j.1365-2141.2001.03081.x
|View full text |Cite
|
Sign up to set email alerts
|

Internal jugular vein thrombosis after assisted conception therapy

Abstract: Superovulation therapy during assisted conception may result in a hypercoagulable state. Five cases of upper extremity venous thrombosis were identified in women who conceived after ovarian stimulation for in vitro fertilization (IVF). They presented between 7 and 10 weeks' gestation with neck pain and swelling. Three had been treated for ovarian hyperstimulation syndrome and two had evidence of inherited thrombophilia. Four patients received thromboprophylaxis before presentation. Although thrombosis is an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 8 publications
0
40
0
Order By: Relevance
“…Thomas et al [12] reported the first case of internal jugular vein thrombosis following in vitro fertilization in a woman with protein S deficiency and heterozygosity for the prothrombin 3Ј UTR mutation, despite anticoagulation with heparin. In October 2001, Arya et al [13] published 5 cases of internal jugular vein thrombosis after assisted conception therapy, two of which had evidence of inherited thrombophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al [12] reported the first case of internal jugular vein thrombosis following in vitro fertilization in a woman with protein S deficiency and heterozygosity for the prothrombin 3Ј UTR mutation, despite anticoagulation with heparin. In October 2001, Arya et al [13] published 5 cases of internal jugular vein thrombosis after assisted conception therapy, two of which had evidence of inherited thrombophilia.…”
Section: Discussionmentioning
confidence: 99%
“…However, prophylactic treatment with heparin or even full treatment with low molecular weight heparin at the time of ovarian hyperstimulation syndrome did not prevent development of upper extremity deep vein thrombosis in some of the patients (9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 92%
“…The number of women treated with assisted reproductive technologies is increasing and often these women have additional risk factors for thrombosis such as age over 35 years. The most common site for thrombosis in this situation is the internal jugular vein presenting with neck pain and swelling [9]. Thus, a thrombosis risk assessment should be undertaken in women undergoing ovarian stimulation with gondotrophins and appropriate thromboprophylaxis should be provided if the risk of thrombosis is considered significant.…”
Section: Introductionmentioning
confidence: 99%